A plant Lysin Motif Receptor-Like Kinase plays an ancestral function in mycorrhiza - Eve Teyssier; Sabine Grat; David Landry; Mathilde Ouradou; Mélanie K. Rich; Sébastien Fort; Jean Keller; Benoit Lefebvre; Pierre-Marc Delaux; Malick Mbengue (Proceedings of the National Academy of Sciences, 2025)
Arbuscular mycorrhiza (AM) with soilborne Glomeromycota fungi was pivotal in the conquest of land by plants almost half a billion years ago. In flowering plants, it is hypothesized that AM is initiated by the perception of AM fungi-derived chito- and lipochito-oligosaccharides (COs/LCOs) in the host via Lysin Motif Receptor-Like Kinases (LysM-RLKs). However, it remains uncertain whether plant perception of these molecules is a prerequisite for AM establishment and for its origin. Here, we made use of the reduced LysM-RLK complement present in the liverwort Marchantia paleacea to assess the conservation of the role played by this class of receptors during AM and in CO/LCO perception. Our reverse genetic approach demonstrates the critical function of a single LysM-RLK, MpaLYKa, in AM formation, thereby supporting an ancestral function for this receptor in symbiosis. Binding studies, cytosolic calcium variation recordings and genome-wide transcriptomics indicate that another LysM-RLK of M. paleacea , MpaLYR, is also required for triggering a response to COs and tested LCOs, despite being dispensable for AM formation. Collectively, our results demonstrate that the perception of symbionts by LysM-RLK is an ancestral feature in land plants, and suggest the existence of yet-uncharacterized AM fungi signals.